Status of living of slums-dwellers in Varanasi city - Darshan Kumar Jha,; Vinod Kumar Tripathi, (National Geographical Journal of India, 2021)
Rapid urbanisation and the insufcient infrastructure and basic urban services in cities have led to the proliferation of slums in India. As per the Census of India 2011, 2613 towns reported slums having 65 million dwellers. Varanasi is not an exception to this pattern. Slum locations are spread all over the city. The objective of this paper to study and analyze the distribution of slums in Varanasi city. The paper also aims to study characteristics of slums including education, health and quality of life dimensions. The paper is based on secondary as well as primary data. Primary data were collected through an interview schedule by a eld survey of 384 households in selected sample slum clusters. The paper presents the spatial distribution of slums in Varanasi City and reviewed the condition of slums based on secondary and primary data and provides a microlevel inter zonal in-depth analysis of Quality of life in slums of the city.